Полиморфизм С1858Т гена PTPN22 и латентный аутоимунный сахарный диабет взрослых - Shtandel, S.A.; Tikhonova, T.M.; Fedets, M.I.; Barylyak, I.R. (Ендокринологія | Endokrynologia, 2020)
Полиморфизм С1858Т гена PTPN22 и латентный аутоимунный сахарный диабет взрослых